RGPDB: database of root-associated genes and promoters in maize, soybean, and sorghum. (8th June 2020) - Moisseyev, Gleb; Park, Kiyoul; Cui, Alix; Freitas, Daniel; Rajagopal, Divith; Konda, Anji Reddy; Martin-Olenski, Madalayne; Mcham, Mackenzie; Liu, Kan; Du, Qian; Schnable, James C; Moriyama, Etsuko N; et al.
Abstract: Root-associated genes play an important role in plants. Despite the fact that there have been studies on root biology, information on genes that are specifically expressed or upregulated in roots is poorly collected. There exist very few databases dedicated to genes and promoters associated with root biology, preventing effective root-related studies. Therefore, we analyzed multiple types of omics data to identify root-associated genes in maize, soybean, and sorghum and constructed a comprehensive online database of these genes and their promoter sequences. This database creates a pivotal platform capable of stimulating and facilitating further studies on manipulating root growth and development. Database URL: https://crri.unl.edu/databases and http://sysbio.unl.edu/RGPDB/ .